Epidemic Situation of Tuberculosis (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
Tuberculosis continues to be a complex socio-economic and medical-biological problem in all countries of the world, including in Uzbekistan. This is due to the increase in the incidence of tuberculosis not only in developing, but also in economically highly developed countries.